Comparing the Effects of Dry-Land and In-Water Core Stability Training Programs on Swimmers’ Upper Body Balance and Performance - Javad Harati; Hassan Daneshmandi; Mohammad Reza Shahabi Kaseb (Biyumikānīk-i varzishī)
Objective: Swimming is a sport that requires a considerable strength, endurance, mobility and stability of the upper body. Therefore, the aim of this study was to compare the effects of dry-land and in-water core stability training programs on swimmers’ upper body balance and performance. Methods: The available statistical sample of this study included 28 swimmers from city of Sabzevar who were divided randomly into three groups of dry-land (10 swimmers), in-water (10swimmers) and control (8 swimmers). Data analysis was done by split-plot ANOVA to compare intra- and inter-group variables and Bonferroni post-hoc test was also utilized to compare group means within two groups. Results: The results showed that four-week core stability exercises on dry-land led to 50m swimming time improvements as well as upper body balance of dominant and non-dominant limbs. There was no significant improvement in 50m for dry-land group and no significant improvement in stroke rate for both experimental groups.  Conclusion: Based on the findings of this study, it is suggested that coaches and swimmers utilize exercises used in this study in order to improve upper body balance as well as swimming performance in their training program.